Introduction - Nawaf Al-Tamimi (17902240) (2023)
This chapter presents the introductory remarks about the book and its content. In so doing, the chapter describes the blockade of Qatar and the ways in which Qatari government reacted to it. The authors describe different analytical perspectives and arguments put forward to understand Qatari policies in order to respond to the blockade. The chapter ends with an overview of the content of different chapters and the organization of the study. Other Information Published in: Qatar’s Nation Branding and Soft Power : Exploring the Effects on National Identity and International Stance License: http://creativecommons.org/licenses/by/4.0/ See chapter on publisher's website: http://dx.doi.org/10.1007/978-3-031-24651-7_1 Additional institutions affiliated with: School of Psychology and Social Work - DI